2016
DOI: 10.1182/blood.v128.22.5371.5371
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ibrutinib Via Nasogastric (NG) Tube & Percutaneous Endoscopic Gastrostomy (PEG) Tube

Abstract: We describe the successful administration of ibrutinib via nasogastic (NG) tube & percutaneous endoscopic gastrostomy (PEG)tube. It was not previously known by the manufacturer if this route of administration was possible. Our patient was a 71 year old man diagnosed with a leukaemic variant mantle cell lymphoma. He was commenced on R-CHOP (rituximab, cyclophospahmide, doxorubicin, vincristine, prednisolone) chemotherapy however after 3 cycles of chemotherapy there was no reduction in his lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For example, of the five drugs in our review where data for NG tube administration is available (ibrutinib, imatinib, tretinoin, vemurafenib, vismodegib), they are supported exclusively by case reports, which did not always provide preparation or administration instructions or lacked detailed information on administration or resulting outcomes. [64][65][66][67][68][69][70][71][72][73][74][75] Additionally, aside from one case report, all of the data described gastric administration, either through an NG, PEG, or gastrostomy tube. This limits some applicability to alternative sites of delivery (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, of the five drugs in our review where data for NG tube administration is available (ibrutinib, imatinib, tretinoin, vemurafenib, vismodegib), they are supported exclusively by case reports, which did not always provide preparation or administration instructions or lacked detailed information on administration or resulting outcomes. [64][65][66][67][68][69][70][71][72][73][74][75] Additionally, aside from one case report, all of the data described gastric administration, either through an NG, PEG, or gastrostomy tube. This limits some applicability to alternative sites of delivery (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports describe successful use of ibrutinib through an NG tube or PEG tube; method of administration not described. 64,65 One report noted that the capsule was opened and flushed down the feeding tube with water. 65 Imatinib X Not available.…”
Section: Alectinibmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case published describing the administration of ibrutinib through a nasogastric tube to a comatose patient. It is worth noting, however, that one case was reported describing the administration of ibrutinib capsule content through the nasogastric tube in a conscious patient with a swallowing disorder [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review revealed only two case reports of patients opening the capsule formulation and administration via NG or PEG tube. 3,6 It was decided to extrapolate this data and direct the assisted living facility to open the capsules and sprinkle over soft food. The caregiver donned appropriate PPE including gloves and mask while administering to the patient.…”
Section: Case Reportmentioning
confidence: 99%
“…5 To date, there are only 2 published case reports of capsule contents being opened and given via nasogastric (NG) tube or percutaneous endoscopic gastrostomy (PEG) tube. 3,6 For patients who cannot swallow, and who are not candidates for alternative intravenous therapies, the safety and efficacy of alternative oral administration of ibrutinib remains unknown.…”
Section: Introductionmentioning
confidence: 99%